The top 5 entrepreneurs / Rafidah Abd Karim … [et al.] - Abd Karim, Rafidah; Awaludin, Farahidatul Akmar; Saad, Nurul Huda; Awaludin, Fazlin (Division of Research, Industrial Linkages and Alumni, UiTM Cawangan Melaka, 2013)
Recently, our country has encouraged more people to be involved in Small Medium Enterprises (SMEs) and become an entrepreneur. Thus, our group has designed a product which can help people to envision their mind, encourage and educate people to become an entrepreneur in future. The special feature about this product is a fun and educational role-playing game (RPG) that can play in a small group. Besides that, it is suitable for students to enhance the entrepreneurship education and also for language learning. Moreover, this product also would in still entrepreneur skills and entity values for entrepreneurships. This product provides people and also students' experience through playing this simulation game of real-world business. The innovative product is expected to have a good commercial value for young learners, educators, potential entrepreneurs and also for the government and private sectors.